PROPAGATION OF ACOUSTIC WAVES THROUGH ELASTIC STRATIFIED MEDIUM WITH HETEROGENEITY IN THE FORM OF RECTANGULAR RESERVOIR - S. A. Mirakyan
The problem of propagation of acoustic waves in an elastic-liquid stratified medium with horizontal-heterogeneous structure in the upper stratum is considered. In the presence of heterogeneity in the form of a rectangular reservoir in the upper elastic stratum a solution of the wave equation by the method of reflected waves in combination with the matrix method is constructed. Analysis of derived solutions allows to determine the conditions under which at a certain amplitude of the incident wave the maximum amplitude of acoustic wave in the liquid stratum is gained.
Keywords: Physics; Acoustics